Penambahan Arang Batok Kelapa pada Produksi Biogas Campuran Kotoran Ayam dan Kotoran Sapi - Haryanto, Agus; Putri, Laily Rahmadani; Suharyatun, Siti; Telaumbanua, Mareli (abe.fp.unila.ac.id, 2023)
This study aims to determine the effect of adding coconut shell biochar on biogas production from a mixture of chicken manure and cow manure. The research was conducted using a batch type digester with an active volume of 2000 mL. The substrate consists of a mixture of chicken manure and cow manure with a weight ratio of 1:1 and 3:1. Biochar from coconut shells is mashed and added at a rate of 3 grams. Parameters observed included ambient temperature, initial and final pH, biogas production and methane content in biogas. The results showed that the addition of coconut shell charcoal had a negative effect which was marked by a decrease in cumulative biogas production. The highest cumulative biogas production was obtained in the treatment without the addition of biochar, both K1B0 and K2B0. Biogas from the K2B0 treatment has a higher CH4 content than those of other treatments. Keywords: Biogas Production, Methane, pH, Substrate Rasio, Temperature